2021
DOI: 10.1186/s40529-021-00316-7
|View full text |Cite
|
Sign up to set email alerts
|

LED light sources improved the essential oil components and antioxidant activity of two genotypes of lemon balm (Melissa officinalis L.)

Abstract: Background Nowadays, light-emitting diodes (LEDs) as a new lighting technology, have been emerged as an alternative source of light for plants due to their wavelength specificity, the narrow width of their bands, small size, solid structure, long lifetime, and low heat generation. Here we investigated the effect of different LED light sources on the essential oil components and antioxidant activity of Melissa officinalis. Two genotypes of lemon balm (Ilam and Isfahan) were subjected to four art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…was highest under combined red and blue LED light (70/30%) compared to normal growing conditions [ 109 ]. Likewise, the combination of red and blue LED light increased the fresh and dry weights of the shoots and the leaf numbers of lemon balm ( Melissa officinalis ) compared with red light alone, blue light alone, or white light [ 110 ]. Another study showed that the leaf and shoot numbers of coriander ( Coriandrum sativum ), as well as its fresh and dry mass, increased under different ratios of red: blue compared with red light alone [ 111 ].…”
Section: Impact Of Abiotic Stresses On Mapsmentioning
confidence: 99%
“…was highest under combined red and blue LED light (70/30%) compared to normal growing conditions [ 109 ]. Likewise, the combination of red and blue LED light increased the fresh and dry weights of the shoots and the leaf numbers of lemon balm ( Melissa officinalis ) compared with red light alone, blue light alone, or white light [ 110 ]. Another study showed that the leaf and shoot numbers of coriander ( Coriandrum sativum ), as well as its fresh and dry mass, increased under different ratios of red: blue compared with red light alone [ 111 ].…”
Section: Impact Of Abiotic Stresses On Mapsmentioning
confidence: 99%
“…LEDs with different wavelengths and energy density (flounce) of light can provide various environmental conditions that influence plant metabolism. Some LED frequencies can be used as signaling factors to increase the essential oils and polyphenolic compounds content [10]. The use of LEDs to improve phytochemical composition has been reported in many medicinal and aromatic plants, including Thymus vulgaris [11], Melissa officinalis [10], Ocimum basilicum [12], Perovskia abrotanoides [13], and Mentha longifolia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Light characteristics modulation can change phytochemical composition, improving plant properties. In selected genotypes of Mentha spicata exposed to red + blue LED light, a higher concentration of monoterpenes was observed in EO than in sunlight, improving its antioxidant activity [10] . Besides, a ratio of 70 % red and 30 % blue wavelengths increased Mentha piperita essential oil yield up to four times, along with increases in plant and fresh weight compared with field conditions [11] .…”
Section: Introductionmentioning
confidence: 94%